Oxidative stress index of porcine follicular fluid influences meiotic maturation and embryo development during in vitro culture - Bin Liu; Takeshige Otoi; Zhao Namula; Oky Setyo Widodo; Maki Hirata; Aya Nakai; Qingyi Lin; Yuichiro Nakayama; Megumi Nagahara; Fuminori Tanihara (Veterinary World, 2025)
Background and Aim: Porcine follicular fluid (pFF) is frequently used to mimic the follicular microenvironment during in vitro maturation (IVM) of oocytes. However, the influence of oxidative stress levels within pFF on oocyte quality and embryo development remains unclear. This study aimed to investigate how varying oxidative stress index (OSI) of pFF affect porcine oocyte meiotic progression, fertilization, and embryonic development during IVM.